Towards an Immunoanalytical Systems for Hepatitis a Virus Determination. (2017) - Micheli, Laura; Fasoli, Andrea; Attar, Aisha; Donia, Domenica T.; Divizia, Maurizio; Amine, Aziz; Palleschi, Giuseppe; Carballo, Pedro A. Salazar; Moscone, Danila
Abstract: Water-borne viral diseases pose high risks for public health worldwide. The conventional biological water quality indicators do not provide adequate information about the presence of pathogenic viruses. In this work a cost effective and rapid system is designed for Hepatitis A virus monitoring in food. A sandwich Enzyme Linked Immuno Magnetic assays is proposed. This system is based on the use of new polydopamine-modified magnetic nanobeads as solid support for the immunochemical chain, and screen printed electrodes as a sensing platform. This rapid, sensitive and low-cost analysis method involves the use of a portable instrument, able to perform measurements directly in the field.